(untitled) (Mustansiria Dental Journal, 2018)
This study aims to investigate the role of using dried Human Amniotic Membrane (dHAM) on rabbit’s oral mucosal wound healing in its early stages. Six male rabbits were used in this study. In each rabbit, two elliptical incisions were done on both sides of tongue dorsum; one of them was left uncovered and the other was covered by dHAM. The animals were divided into two groups with three rabbits each according to the sacrifice periods which were three days and one week. After sacrifice, histopathological examination was performed to assess re-epithelialization and inflammation. Within the first three days, the re-epithelialization was much more faster in dHAM group than that in control one, and the difference between the control and study group was statistically highly significant ( p=0.005 <0.01). Moreover, the rate of inflammatory process show significant difference between the two groups with advantage to HAM group (p =0.046 <0.05). However, after one week, this difference was statistically non-significant ( p =0.317 > 0.05). Human Amniotic Membrane could be considered as an option to enhance oral wound healing especially in its early stages.